Powder processing and In Vivo evaluation of a titanium porous coating implant - Oliveira, M. V.; Vasconcellos, Lmr [UNESP]; Carvalho, Y. R. [UNESP]; Cairo, Caa; Pereira, L. C.; Campos, J. B. (My University, 2004)
The processing of titanium porous coatings using powder metallurgy technique to achieve a porous structure that allows osseointegration with bone tissue was discussed. The porous microstructure exhibited micropores and interconnected macropores with size ranges that allowed bone ingrowth. The macropores in the coatings were originated from the binder evaporation while the micropore was related with the porous titanium powder and the low compaction pressure used. The in vivo evaluation indicated that osseointegration had occurred between the bone and porous material.
Keywords: Bone; Evaporation; Histology; Implants (surgical); Microstructure; Porosity; Porous materials; Powder metallurgy; Powders; Pressure effects; Sintering; Tissue; Titanium; Bone tissues; Osseointegration; Porous coatings; Porous structure; Coatings